lntussusception at the Pediatric Ward of Dr. Pirngadi Hospital, Medan - Lubis, Azwan Hakmi; Sinuhaji, Atan Baas; Sutanto, A. H.; Yosodiharjo, Asmui (Indonesian Pediatric Society, 1990)
A retrospective study had been conducted on hospitalized infants and children in the Pediatric ward of Dr. Pirngadi Hospital, Medan from January 1, 1987 through December 31, 1988. The purpose is to assess the incidence and clinical manifestations of intussusception. During the same period, there were 6484 infants and children hospitalized, 39 (0.6%) with intussusception, consisting of 23 (58.9%) males and (41.1%) females. Most of the cases (53.85%) were in the age group of 4-6 months. Thirty four patients (87,12%) were well-nourished, and 5 patients (12.82%) were undernourished. The major symptoms of intussusception were bloody diarrhoea (87.17%), vomiting (82.05%) and abdominal distention (66.41%). Successful reposition with barium enema occured in I (20%) out of 5 patients. The major symptoms of intussusception were bloody diarrhoea (87.17%), vomiting. Surgical intervention was performed in 22 patients (56.41%). The result was as follows: discharged in good condition in 15 (68.18%) and deaths occurred in the remaining cases (7 cases = 31.82%). Of those 7 cases who died after operation, 2 cases were hospitalized in less than 2 days, 3 cases in less than 3 days and the remaining 2 cases in more than 3 days, after the symptoms developed.